2018
DOI: 10.1111/echo.14181
|View full text |Cite
|
Sign up to set email alerts
|

Identification of significant coronary artery disease in patients with non‐ST segment elevation acute coronary syndrome by myocardial strain analyses using three‐dimensional speckle tracking echocardiography

Abstract: Background Speckle‐tracking imaging is a novel method for assessing left ventricular function and ischemic changes. This study aimed to predict the presence of significant coronary artery stenosis in patients with non‐ST‐segment elevation acute coronary syndrome (NSTE‐ACS) by 3D strain analysis using speckle tracking echocardiography (3DSTE) at rest. Methods This cross‐sectional study included a total 60 patients with NSTE‐ACS who underwent 3DSTE immediately prior to coronary angiography. Subsequently, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The patients were categorized upon presence of signi cant stenosis in the coronary angiography to two groups. (21) All strain parameters were signi cantly reduced in patient group of signi cant stenosis. Receiver operating characteristic (ROC) curve analysis demonstrated that GPSLS could effectively detect patients with signi cant stenosis (area under ROC curve = 0.840, 95% CI = 0.735-0.945).…”
Section: Discussionmentioning
confidence: 88%
“…The patients were categorized upon presence of signi cant stenosis in the coronary angiography to two groups. (21) All strain parameters were signi cantly reduced in patient group of signi cant stenosis. Receiver operating characteristic (ROC) curve analysis demonstrated that GPSLS could effectively detect patients with signi cant stenosis (area under ROC curve = 0.840, 95% CI = 0.735-0.945).…”
Section: Discussionmentioning
confidence: 88%
“…We used a conventional AVA index of .6cm 2 /m 2 as the cutoff value 20 for severe AS, and the AVA index was significantly reduced in all members of the AS group compared to control (.29 ± .10cm 2 /m 2 compared to 2.03 ± .18cm 2 /m 2 , p < .001).Among the 2D echocardiographic findings (Table 3), the interventricular septum (IVS) and posterior wall were found thicker in patients with AS than in the controls (…”
Section: Resultsmentioning
confidence: 99%
“…Standard 3D STE was performed. 20 In the final phase, automated 3D STE strain analyses were presented as curves with color-coded LV 17 segments in a bull's-eye plot. 21 As weighted averages of the regional values from the 17 myocardial segments, global values for longitudinal, circumferential, radial, and area strains were calculated.…”
Section: D Speckle Tracking Echocardiographymentioning
confidence: 99%
“…GLS was demonstrated to effectively identify patients with significant stenosis via receiver operating characteristic curve analysis (area under ROC curve = 0.840, 95% confidence interval = 0.735–0.945). GLS with a cutoff value of −13.50% showed good sensitivity and specificity for detecting significant stenosis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%